Nexus among Crypto Trading, Environmental Degradation, Economic Growth and Energy Usage: Analysis of Top 10 Cryptofriendly Asian Economies - Astini, Rina; Ishrat, Kehkashan; Ramli, Yanto; Tafiprios, Tafiprios; Chong, Kwong Wing; Keong, Ooi Chee (International Journal of Energy Economics and Policy, 2023)
The higher discharge of carbon emissions in environment is endangering human life as well as eco system. With the emergence of digital technology, crypto trading and blockchain technologies are also causing the paradigm shift in technological needs, however, in parallel, creating unresolved environmental problems especially in the top 10 crypto-friendly Asian economies due to the higher percentage of poisonous emissions. Thereby, the study attempts to scrutinize the nexus among crypto-trading, environmental degradation, economic growth and energy usage. CO2 emissions are taken as a proxy of environmental degradation in the context of crypto friendly Asian economies. The data extracted from WDI and coin market cap covering the period from 2012-2020. The article applied CS-ARDL technique in order to find the association between variables in short and long run. Granger Causality test is also applied to find out the causality among constructs. Findings expose that bi-directional causality exists between crypto trading and carbon emission and crypto trading and energy usage, hence, disturbing environmental sustainability due to high emissions. The paper suggests policy makers and other institutional officers to de-socialize those block chain technologies which consumes high energy and use green technology as their substitute. This helps in the reduction of environmental damages.